A disk-type dose imaging detector based on blue and orange RPL in Ag-activated phosphate glass for 2D and 3D dose imaging applications. (December 2015) - Kurobori, Toshio; Takemura, Akihiro; Miyamoto, Yuka; Maki, Daisuke; Koguchi, Yasuhiro; Takeuchi, Nobuhiro; Yamamoto, Takayoshi; Chen, Yao Qiang
Abstract: A disk-type two- and three-dimensional (2D, 3D) X-ray dose imaging detector was developed based on the radiation-induced silver (Ag)-related species in Ag-activated phosphate glass. This luminescent detector is based on the blue and orange radiophotoluminescence (RPL) phenomena. A comparative study of the steady- and transient-state optical properties of blue and orange RPL, such as the time-resolved luminescence spectra and the RPL decay curves, was performed. In addition, the combination of a confocal optical detection system with a transparent glass detector enables 3D reconstruction through the stacking of dose images collected at different depths within the material. The capabilities of this detector for 2D and 3D dose imaging applications are discussed. Highlights: A disk-type 2D and 3D dose imaging detector based on RPL was developed. The steady- and transient-state properties of the blue and orange RPL were presented. The RPL detector is useful for fluorescent nuclear track detection.